The 2017 FIDIC contracts - Godwin, William H., 1957- (Hoboken : Wiley-Blackwell, 2019)
"The aim of the proposed book is to set out and discuss the main new features of the 2nd edition of the three Books in order to provide FIDIC users with a concise guide to the new forms. This will provide essential guidance as the international construction industry begins to use the new forms, which are expected to have significant differences in key clauses when compared to the current FIDIC contracts"--
Includes index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Construction contracts; Engineering contracts; Architectural contracts; Contracts (International law); Standardized terms of contract; Contrats (Droit international); Contrats types; Architectural contracts; Construction contracts; Contracts (International law); Engineering contracts; Standardized terms of contract